The Spirit of Entrepreneurship and the Obstacles Faced by SMPN Students of Banda Aceh in Learning Entrepreneurship - Rizka Rizka; Nurfiani Syamsuddin; Fahmi Arfan (International Conference on Multidisciplinary Research, 2022)
The purpose of this research was to find out how the quality of entrepreneurship learning materials affects students’ entrepreneurial spirit and the obstacles faced in building the entrepreneurial spirit amongthe students of State Junior High School (SMPN) in Banda Aceh City. To obtain maximum results, this research used two approaches, namely quantitative and qualitative approaches. A quantitative approach was used to measure the material and the effect of learning on students' enthusiasm after attending the lesson. Meanwhile, a qualitative approach was used to find accurate data about the obstacles faced in increasing the entrepreneurial spirit of students. Considering that the population was quite large, the data was taken from only 6 public junior high schools with a total population of 1400 people.The sample was taken using the purposive-sampling system.According to the specified sampling formula, the number of data sources was 149 students. The results of the study showed that the learning materials were not satisfactory so that they were unable to influence the students' spirit of entrepreneurship.There were some basic obstacles in learning entrepreneurship material which became one of the factors for the low entrepreneurial spirit of junior high school students in Banda Aceh City. Keywords: learning, entrepreneurial spirit, obstacles